PENERAPAN STRATEGI PEMBELAJARAN BENAR SALAH BERANTAI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SDN 024 TARAI BANGUN KABUPATEN KAMPAR - Murni Murni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the lack of IPS learning outcomes student class VI SDN 024 Tarai Bangun Kabupaten Kampar. This study aims to determine the increase IPS learning outcomes student class VI SDN 024 Tarai Bangun Kabupaten Kampar. Application of learning strategies completely wrong serial held for 1 month. The subjects were grade VI SDN 024 Tarai Bangun Kabupaten Kampar by the number of students as many as 46 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research, the conclusion of the current study is based on the results of student learning in social studies, the prior action learning outcomes of students classified as not yet complete or has not been successful, with classical completeness students who completed was 37%, or only 17, after the applied strategy cooperative learning really one chain students who completed the first cycle increased compared to prior to the action, but the first cycle also can not be said to be successful, because the classical completeness students who completed was 63%, or 29 students who completed, the second cycle student learning outcomes increased with classical completeness 87%, which means that research can be said to be successful.